Evolution of Listeria monocytogenes During a Persistent Human Prosthetic Hip Joint Infection - Muchaamba, Francis; Eshwar, Athmanya K.; von Ah, Ueli; Stevens, Marc J. A.; Tasara, Taurai (Frontiers in Microbiology, 2020)
Listeria monocytogenes associated prosthetic joint infections (PJI) are a rare but increasing clinical problem of listeriosis. We characterized two isolates of the same L. monocytogenes strain isolated within five years of each other from a recurrent human prosthetic joint infection. The two isolates although clonally identical were phenotypically distinct confirming that the original infection strain had evolved within the human host PJI environment giving rise to a phenotypic distinct variant. The recurrent PJI isolate displayed various phenotypic differences compared to the parental original PJI isolate including diminished growth and carbon source metabolism, as well as altered morphology and increased stress sensitivity. The PJI isolates were both diminished in virulence due to an identical truncation mutation in the major virulence regulator PrfA. Genome wide sequence comparison provided conclusive evidence that the two isolates were identical clonal descendants of the same L. monocytogenes strain that had evolved through acquisition of various single nucleotide polymorphisms (SNPs) as well as insertion and deletion events (InDels) during a persistent human PJI. Acquired genetic changes included a specific mutation causing premature stop codon (PMSC) and truncation of RNAse J1 protein. Based on analysis of this naturally truncated as well as other complete RNAse J1 deletion mutants we show that the long-term survival of this specific L. monocytogenes strain within the prosthetic joint might in part be explained by the rnjA PMSC mutation that diminishes virulence and activation of the host immune system in a zebrafish embryo localized infection model. Overall our analysis of this special natural case provides insights into random mutation events and molecular mechanisms that might be associated with the adaptation and short-term evolution of this specific L. monocytogenes strain within a persistent human PJI environment.